2023
DOI: 10.1186/s40545-023-00591-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between drug pricing and drug shortage in Saudi Arabia: a retrospective database analysis

Abstract: Background Previous studies have suggested that drug pricing could contribute to drug shortages; however, there is limited quantitative assessment of this potential causal association. This retrospective database analysis aimed to investigate the association between drug prices and drug shortage incidents in Saudi Arabia. Methods This was a retrospective database analysis study. Drugs with shortage notifications sent to the Saudi Food and Drug Auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…According to a 2019 survey by the European Association of Hospital Pharmacists, medical professionals have identified price as a significant cause of drug shortages ( Miljković et al, 2020 ). Furthermore, research has shown that if a shortage of specific prescription drugs persists, the risk of drug prices rising along with the disruption of patient care increases ( Dave et al, 2018 ), and the risk of drug shortages increases even when domestic drug prices are significantly lower than those in foreign countries ( Alowairdhi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to a 2019 survey by the European Association of Hospital Pharmacists, medical professionals have identified price as a significant cause of drug shortages ( Miljković et al, 2020 ). Furthermore, research has shown that if a shortage of specific prescription drugs persists, the risk of drug prices rising along with the disruption of patient care increases ( Dave et al, 2018 ), and the risk of drug shortages increases even when domestic drug prices are significantly lower than those in foreign countries ( Alowairdhi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%